On paper; in practice: measuring compliance with official pricing policies in a large field study of essential medicines in Indonesia - Ayu Rahmawati; H. U. Ramadaniati; Y. Anggriani; W. Nathanial; E. Pisani (Journal of Pharmaceutical Policy and Practice, 2025)
Background: In 2015, Indonesia Ministry of Health (MoH) issued a decree to ensure the affordability of medicines by providing transparent prices which obliged all manufacturers to print a maximum retail price (MRP) on medicine primary packaging. We measure the compliance of manufacturers and retailers with the regulation stated in the decree and estimate the retailers’ profit.Methods: Five essential medicines (allopurinol, amlodipine, amoxicillin, cefixime, dexamethasone) were purchased from randomly selected health facilities, retail pharmacies and online outlets in Indonesia. We recorded retailer’s selling price and product’s MRP. We also sourced product’s list price and sales volume from pharmaceutical market data. We conducted an MRP policy implementation analysis by evaluating three indicators (retail price transparency, permitted MRP and permitted sales price). We also estimated the retailers’ profit by taking into account the profit margin and sales volume.Results: Of 1249 sampled medicines, nearly all samples (99.4%) had visible MRP on their packaging indicating high transparency compliance. For unbranded generics, none complied with permitted MRP with a median ratio of printed MRP to permitted MRP being 3.5 (IQR 2.6–7.9), whilst higher compliance (11.2%) was observed for branded generics (IQR 1.1–1.7, median 1.1). 33% of the samples were sold above the printed MRP with the lowest compliance to actual selling price being documented in hospitals. Branded generics accounted for 79% of the product value across the study medicines and generated more profits than the unbranded versions.Conclusion: The transparency implementation through printed MRP and the compliance with permitted sales price regulation contribute to retailer accountability. Rules restricting permitted MRPs for unbranded generics, irrational since their inception, while they never set any limits at all on the price of branded medicines. This showed not enough evidence that the policy contributed to its objective of ensuring affordability.